THE PRINCIPALS' ROLE IN THE ELEMENTARY SCIENCE PROGRAM. - Ploutz, Paul F. (Science Education, 1963)
The article examines the role of the principal in the elementary science program in the United States. The elementary principal is expected to accept his share of responsibility, citing the significance of one's involvement in creating interest and in affecting change in student's behavior. The principal must also assure each student the opportunity to develop his potential in science. And local schools still hold great responsibility of providing an updated science program continual from the kindergarten through the twelfth grade.